Functional capacity of natural killer cells in HTLV-1 associated myelopathy/tropical spastic paraparesis - Queiroz, Gabriel Andrade Nonato; Mascarenhas, Rita Elizabeth Moreira; Vieillard, Vincent; Andrade, Raphaela Lisboa; Galvão-Castro, Bernardo; Grassi, Maria Fernanda Rios (BMC infectious diseases, 2019)
Natural killer (NK) cells are part of the innate immune system and provide surveillance against viruses and cancers. The ability of NK cells to kill virus-infected cells depends on the balance between the effects of inhibitory and activating NK cell receptors. This study aimed to investigate the phenotypic profile and the functional capacity of NK cells in the context of HTLV-1 infection. This cross-sectional study sequentially recruited HTLV-1 infected individuals with HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP) and asymptomatic HTLV-1 (AS) from the Integrated and Multidisciplinary HTLV Center in Salvador, Brazil. Blood samples from healthy blood donors served as controls. NK cell surface receptors (NKG2D, KIR2DL2/KIR2DL3, NKp30, NKG2A, NKp46, TIM-3 and PD-1), intracellular cytolytic (Granzyme B, perforin) and functional markers (CD107a for degranulation, IFN-[gamma]) were assayed by flow cytometry in the presence or absence of standard K562 target cells. In addition, cytotoxicity assays were performed in the presence or absence of anti-NKp30. The frequency of NKp30.sup.+ NK cells was significantly decreased in HAM/TSP patients [58%, Interquartile Range (IQR) 30-61] compared to controls (73%, IQR 54-79, p = 0.04). The production of cytolytic (perforin, granzyme B) and functional markers (CD107a and IFN-[gamma]) was higher in unstimulated NK cells from HAM/TSP and AS patients compared to controls. By contrast, stimulation with K562 target cells did not alter the frequency of CD107a.sup.+ NK cells in HAM/TSP subjects compared to the other groups. Blockage of the NKp30 receptor was shown to decrease cytotoxic activity (CD107a) and IFN-[gamma] expression only in asymptomatic HTLV-1-infected individuals. NK cells from individuals with a diagnosis of HAM/TSP present decreased expression of the activating receptor NKp30, in addition to elevated degranulation activity that remained unaffected after blocking the NKp30 receptor.